The Role of Accounting Student Learning Experience on Career Choices as Public Accountants: The Effects of Information Overload and Alternative Attractiveness - Ovy Alexander; Sriwidharmanely Sriwidharmanely (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research project aims to delve deeper into the impact of experiential learning, the challenge of information overload, and alternative career appeal when individuals decide to pursue a career as a public accountant. This study employs Cognitive Load Theory (CLT) to explore the roles of information overload and alternative career attractiveness in individuals' decisions regarding public accounting careers based on their learning experience, which motivated them. The research methodology involves the administration of a questionnaire, with participants selected through random sampling from a pool of accounting students. The study employs Moderated Regression Analysis (MRA) to examine the relationships between these variables. The findings indicate a significant association between information overload and its reinforcement of the role of experiential learning in career choice among accounting students. In contrast, alternative career attractiveness does not exhibit a meaningful relationship. It appears to weaken the influence of learning experience in their decision-making process regarding a career as a public accountant.